The Counselor Brent Scowcroft and his Role in Achieving the Requirements of the American National Security (Journal of the College of Education for Women, 2023)
Despite the multiplicity of institutions contributing to the decision-making process in the United States of America, they interact to crystallize positions regarding international and strategic situations. The formulation of the national security policy depends on a number of institutions that complement each other in order to achieve an advanced security situation. Thus, the decision reflects the process of interaction of the existing regulatory institutions. This is because the essence of the national security and achieving its requirements also stems from the existence of a coherent system of shared beliefs and principles in the American society. Besides, these elements are the bases for achieving security. Researching about Brent Scowcroft’s role in meeting the requirements of the united States’ national security, it has been found necessary to include two pivots to the study. The first pivot discusses the requirements of achieving the national security of the United States of America, whereas the second pivot tackles Brent Scowcroft’s role, through the mechanisms of the national security council, in achieving the national security requirements in particular within the decision-making process in the history of the contemporary American political system. As for the type of the study, it is a historical study within the axis of contemporary American politics, while the methodology of the study came within the scientific analysis and according to the narrative and descriptive historical approach. This is because the research problem emphasizes the identification of the security and military requirements in order to achieve the integration of the national security of the United States. Finally, the conclusions have verified the National Security Adviser’s prominent role of during the Scowcroft era, in conducting partnership with the Ministry of Foreign Affairs in the decision-making process. The latter has said to affect the overall foreign policy and achieve the national security requirements of the United States of America at the end of the last century.